Dystopia as liberation: disturbing femininities in contemporary Thailand. Issue 1 (July 2017) - Harrison, Rachel
Abstract Despite the stereotypical, outsider view of Thailand as a thriving hub of international sex tourism, traditional and local constructions of Thainess instead privilege the position of the 'good' Thai woman—a model of sexual propriety, demure physicality and aesthetic perfection. This is the image of femininity that is heralded by Thailand's Tourist Authority and by government agencies alike as a marketable symbol of cultural refinement and national pride. But this disturbing 'utopian' construction of femininity might for some be considered a dystopia shaped by forms of power centred on elite urban rule. In mainstream definitions of Thainess, the monstrous and grotesque inverses of 'good' womanhood are located in the 'dystopian' visions of rural-based folk traditions that abound with malevolent female spirits and demons, and in the contemporary Thai horror films that draw on these tropes. Adopted by Thai feminists and by street protestors in Bangkok at times of recent political unrest, portrayals of a 'monstrous-feminine' have been adopted as central to a carnivalesque strategy of response and resistance to elite discourses of control. Such forces serve to symbolically disturb and destabilise middle-class constructions of a utopian vision of Thainess with Bangkok as its cultural core. This paper examines instances of how and why the counter-strategy of primitivism and monstrosity has developed, and the extent to which it translates 'dystopian' expressions of female sexuality in new imaginaries of 'dystopia' as a space of liberation from stultifying cultural and political norms.